Stroke epidemiology and outcomes of stroke patients in Nepal: a systematic review and meta-analysis - Raju Paudel; Christine Tunkl; Shakti Shrestha; Ram Chandra Subedi; Ayush Adhikari; Lekhjung Thapa; Bikram Prasad Gajurel; Avinash Chandra; Ghanashyam Kharel; Pankaj Jalan; Subash Phuyal; Babu Ram Pokharel; et al. (BMC Neurology, 2023)
Abstract Background With an increasing burden of stroke, it is essential to minimize the incidence of stroke and improve stroke care by emphasizing areas that bring out the maximum impact. The care situation remains unclear in the absence of a national stroke care registry and a lack of structured hospital-based data monitoring. We conducted this systematic review and meta-analysis to assess the status of stroke care in Nepal and identify areas that need dedicated improvement in stroke care. Methods A systematic literature review was conducted to identify all studies on stroke epidemiology or stroke care published between 2000 and 2020 in Nepal. Data analysis was done with Statistical Package for Social Sciences (SPSS) and Comprehensive Meta-analysis (CMA-3). Results We identified 2533 studies after database searching, and 55 were included in quantitative and narrative synthesis. All analyses were done in tertiary care settings in densely populated central parts of Nepal. Ischemic stroke was more frequent (70.87%) than hemorrhagic (26.79%), and the mean age of stroke patients was 62,9 years. Mortality occurred in 16.9% (13-21.7%), thrombolysis was performed in 2.39% of patients, and no studies described thrombectomy or stroke unit care. Conclusion The provision of stroke care in Nepal needs to catch up to international standards, and our systematic review demonstrated the need to improve access to quality stroke care. Dedicated studies on establishing stroke care units, prevention, rehabilitation, and studies on lower levels of care or remote regions are required.